A decision support model for spare parts inventory in a multi-echelon closed loop supply chain - Sy, Charlle Lee (Animo Repository, 2016)
This research work develops a decision support model for a network design problem concerning a spare parts closed loop supply chain. It involves the formulation of an optimization model that takes on a mid to long-term planning perspective and covers decisions that have lasting and binding impact on organizational performance. These decisions include investment, location assignment, and inventory considerations for the different echelons in the supply chain. The computational studies conducted on the model likewise examine various scenarios and inventory management policies, and their corresponding cost implications to the supply chain. © IEOM Society International.